Pengaruh Profitabilitas, Solvabilitas, Likuiditas dan Aktivitas terhadap Nilai Perusahaan pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2016-2020 - Thoha, Muhammad Nuur Farid; Hairunnisa, Livia (IJOSMAS, 2022)
This research was conducted with the aim to determine the effect of profitability, solvency, liquidity and activity on the value of the company. The population used in this study is manufacturing companies listed on the Indonesia Stock Exchange for the period 2016-2020. The sample selection in this study used purposive sampling techniques by setting several sampling criteria and producing 15 companies that were used as samples from 32 manufacturing companies of food and beverage subs sector during 2016-2020. The analysis tool used in this study is to use multiple linear regression analysis techniques using SPSS version 20 statistics test tool. The results of this study have shown that profitability has a positive and significant effect on the value of the company, while solvency, liquidity and activity have no effect on the value of the company